Evolution of the Ligand Shell Around Small ZnO Nanoparticles During the Exchange of Acetate by Catechol: A Small Angle Scattering Study. Issue 1 (13th December 2018) - Schindler, Torben; Lin, Wei; Schmutzler, Tilo; Lindner, Peter; Peukert, Wolfgang; Segets, Doris; Unruh, Tobias
Abstract: The core‐shell structure of colloids surrounded by ligands is of great importance for their later application as it can significantly alter the chemical and physical properties of the nanoparticles (NPs). A combination of small angle X‐ray and neutron scattering (SAXS/SANS) in the native solution with additional ex situ measurements (titration‐UV) was applied to study the NP/ligand interface of ZnO NPs after functionalization with catechol derivatives. Based on SAXS data, it was found that within the multimodal particle size distribution the fraction of agglomerates is shifted to smaller sizes and nearly disappeared upon the binding of ethyl 3, 4‐dihydroxybenzoate (CAT) molecules. This is ascribed to improved stabilization at the primary particle level by CAT molecules. By combining the neutron scattering contrast with the input of bound CAT molecules from a previously developed titration‐UV method, the heterogeneous composition of the ligand shell became accessible for the first time. Abstract : The core‐shell structure of colloids surrounded by ligands is of great importance for the chemical and physical properties of the nanoparticles (NPs). Herein, we studied the NP/ligand interface of small ZnO NPs after functionalization with catechol derivatives. The heterogeneous composition of the ligand shell consisting out of acetate, catechol and ethanol became accessible for the first time.